Effect of Change in Tilt Angle on the Performance of Photovoltaic Systems - Emmanuel Chinweikpe Obuah; Tamuno-Omie Joyce Alalibo (Journal of Power Electronics and Devices, 2020)
Photovoltaic (PV) system is increasingly required in industries, commercial and domestic buildings. The performance of PV is a problem that needs attention. Many factors contribute to the performance of PV systems. This study presents the effect of change in tilt angle on the performance of PV systems. The system’s location is Port Harcourt. An average yearly load of 2170kWh/day was estimated for the system. Various angles were used for the position of the PV panel on the working plane. It was observed that as the tilt angle increases, the lower the yearly irradiation on global collection planes. Also as the overall system losses reduces, the performance ratio reduced as well. The reduction in the overall system and improvement of the system’s ‘performance ratio was as a result of increase in tilt angle. The ranges of tilt angle selected are: 10o, 15o, 20o, 25o, 30o, 35o, 40o and 45o. The success of this project was achieved using PVSYST tool. It is recommended that the system can be used at a location with similar solar data with study location, Port Harcourt Nigeria.